REALISME MAGIS DALAM FILM MY NEIGHBOR TOTORO KARYA HAYAO MIYAZAKI DAN IMPLIKASINYA DALAM PEMBELAJARAN SASTRA - Likas Amelia Lumban Gaol; Uus Martinus Kamajaya Al Katuuk; Oldie Stevie Meruntu (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
Magical realism is a literary approach that combines realistic and magical elements within a unified narrative framework. Although studies on magical realism have been widely conducted in novels and short stories, research examining magical realism in animated films and its implications for literature learning remains limited. This study aims to analyze the characteristics of magical realism in Hayao Miyazaki’s My Neighbor Totoro based on Wendy B. Faris’s theory and to examine its implications for literature learning at the junior high school level. This research employed a descriptive qualitative approach using observation and documentation techniques for data collection. Data were analyzed through identification, classification, interpretation, and conclusion drawing based on Faris’s five characteristics of magical realism. The findings reveal that My Neighbor Totoro fulfills all five characteristics of magical realism, namely the irreducible element, phenomenal world, merging realism, unsettling doubts, and disruptions of time, space, and identity. The magical elements are naturally integrated into the characters’ everyday reality, creating a strong magical realist narrative. Furthermore, the film has potential as instructional material for fantasy narrative texts in junior high schools because it can enhance students’ imagination, literary appreciation, and character development, including independence, family affection, and mutual assistance. Therefore, My Neighbor Totoro can be utilized as an innovative and contextual medium for literature learning. ABSTRAK Realisme magis merupakan salah satu pendekatan sastra yang memadukan unsur realitas dan unsur magis dalam satu kesatuan naratif. Meskipun kajian realisme magis telah banyak dilakukan pada karya sastra berupa novel dan cerpen, penelitian yang mengkaji realisme magis dalam film animasi serta implikasinya terhadap pembelajaran sastra masih relatif terbatas. Penelitian ini bertujuan untuk menganalisis karakteristik realisme magis dalam film My Neighbor Totoro karya Hayao Miyazaki berdasarkan teori Wendy B. Faris serta mengkaji implikasinya terhadap pembelajaran sastra di SMP. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi dan dokumentasi. Analisis data dilakukan melalui identifikasi, klasifikasi, interpretasi, dan penarikan simpulan berdasarkan lima karakteristik realisme magis Wendy B. Faris. Hasil penelitian menunjukkan bahwa film My Neighbor Totoro memenuhi lima karakteristik realisme magis, yaitu the irreducible element, phenomenal world, merging realism, unsettling doubts, dan disruptions of time, space, and identity. Kehadiran unsur magis dalam film menyatu secara alami dengan realitas kehidupan tokoh sehingga membentuk narasi realisme magis yang kuat. Selain itu, film ini memiliki relevansi sebagai bahan ajar pada materi teks cerita fantasi di SMP karena mampu mengembangkan imajinasi, apresiasi sastra, serta menanamkan nilai-nilai karakter seperti kemandirian, kasih sayang keluarga, dan sikap tolong-menolong. Dengan demikian, film My Neighbor Totoro dapat dimanfaatkan sebagai media pembelajaran sastra yang inovatif dan kontekstual.